2015
DOI: 10.1590/0104-07072015001230012
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of antenatal care for adolescents from state capitals in Southern and Northeastern Brazil

Abstract: Quantitative and descriptive study that intended to describe some aspects of antenatal care for adolescents at teaching hospitals in the South and Northeast of Brazil, based on the quality criteria established by the Humanization Program of Antenatal and Birth Care. This is an excerpt from the research "Social support networks for fatherhood during adolescence". The data collection occurred between December 2008 and December 2009. The sample consisted of 559 puerperal adolescents. The results showed that 98% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
3
0
9
Order By: Relevance
“…They made it possible for the participants to reflect on their gestational process and on the adaptation to hospital routine. Thus, the educational process is not a simple task, because it is not restricted to the transmission of information to pregnant women (18) . On the contrary, it is a shared practice that involves exchange of knowledge, through the establishment of bonds and must be constantly improved.…”
Section: When We Get Information When We Become Aware Of What Is Goimentioning
confidence: 99%
“…They made it possible for the participants to reflect on their gestational process and on the adaptation to hospital routine. Thus, the educational process is not a simple task, because it is not restricted to the transmission of information to pregnant women (18) . On the contrary, it is a shared practice that involves exchange of knowledge, through the establishment of bonds and must be constantly improved.…”
Section: When We Get Information When We Become Aware Of What Is Goimentioning
confidence: 99%
“…Os resultados de um estudo brasileiro mostram que, das cidades pesquisadas, Pelotas (RS) teve maior prevalência de partos na adolescência, perfazendo 21,4% do total de nascimentos no hospital participante da pesquisa, seguida por Florianópolis (SC) com 16,2% e João Pessoa (PB) com 12,9% 21 .…”
Section: Determinantes Sociais Da Saúde E Gravidez Na Adolescênciaunclassified
“…Other studies also report the persistence of the biomedical paradigm in prenatal care practices, with the implementation of traditional lecture-based educational activities merely aimed to convey information and make recommendations that are not consistent with the reality and do not meet the specific needs of the target population (5)(6). The lack of a space for active communication and interaction between health professionals and pregnant women creates obstacles to the development of appropriate prenatal care (7).…”
Section: In the Groups We Talk To Each Other [] We Feel At Ease Wmentioning
confidence: 99%
“…On the other hand, studies carried out in different Brazilian regions showed that prenatal care for teenagers still falls far short of what is recommended, especially with regard to guidance, to the ability to attract the target audience to the groups of pregnant teenagers at an early stage, and to the delivery of permanent care. Guidance/ education activities are neglected because of the large number of tasks performed by health professionals and the limited time available for prenatal consultations (4)(5).…”
Section: Introductionmentioning
confidence: 99%